Description of the shape and position of the condyles in Kennedy classification class I, II, III, and IV patients through panoramic radiography - Sarifah, Norlaila; Andiyah, Angelia Wurie; Taufiqurrahman, Irham; Nurrahman, Tri; Sari, Galuh Dwinta; Sukmana, Bayu Indra (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: Tooth loss occurs when the tooth detaches from the socket. Cases of partial tooth loss can cause differences in the shape and position of the condyles. This study aimed to know the description of the frequency distribution of normal and abnormal condyle shapes and positions in Kennedy classification case patients class I, II, III, IV. Materials and Methods: This research used a cross-sectional descriptive approach. The sample used secondary data from 120 digital panoramic radiographic photos of patients aged 30-70 from January 2018 to January 2024 at Ulin Hospital and Gusti Hasan Aman Hospital Banjarmasin. Results: Based on the research results at RSUD Ulin and RSGM Gusti Hasan Aman Banjarmasin, the round shape was the most common condyle shape found in patients with Kennedy classification, with most condyle positions pointing to the anterior. The change in the shape and position of the condyle becomes pathological due to the long-term loss of part of the tooth. Conclusion: The frequency distribution of the shape and position of the condyle of patients with Kennedy classification class I, II, III, IV was the round shape as the most common condyle shape experienced by patients which is one of the normal condyles shapes, and an abnormal position of TMJ condition pointing anteriorly.